-25-(x+5) = 415 + 5(x-83)
=> -25-x-5=415+5x-415
=> -30-x-5x = 0
=> -30=6x
=> x = -5
`-25-(x+5)=415+5(x-83)`
`<=> -25-x-5=415+5x-415`
`<=> -x-5x=415-415+25+5`
`<=> -6x=30`
`<=> x=-5`
-25 - ( x+5 ) = 415 + 5(x- 83)
\(-25-x-5-415-5x+415=0\)
\(-30-6x=0\)
\(6x=-30\)
\(x=-30:6=-5\)
Vậy x=-5
−25−(x+5)=415+5(x−83)
->−25−x−5=415+5x−415⇔-25-x-5=415+5x-415
->−x−5x=415−415+25+5⇔-x-5x=415-415+25+5
->−6x=30⇔-6x=30
->x=−5
−25−(x+5)=415+5(x−83)-25-(x+5)=415+5(x-83)
⇔−25−x−5=415+5x−415⇔-25-x-5=415+5x-415
⇔−x−5x=415−415+25+5⇔-x-5x=415-415+25+5
⇔−6x=30⇔-6x=30
⇔x=−5